The bell tolls for indeterminant lung nodules: computer-aided nodule assessment and risk yield (CANARY) has the wrong tune - Wilson, David O.; Pu, Jiantao (Journal of Thoracic Disease, 2016)
There is a potential epidemic of indeterminant pulmonary nodules (IPN) with the evolution of low dose computed tomography (LDCT) screening programs for lung cancer. The National Lung Screening Trial (NLST) demonstrated that annual screening with LDCT reduces mortality from lung cancer by 20% in high risk individuals.